EFISIENSI ALOKASI BERDASARKAN MAQOSHID SYARIAH, STUDI KASUS TERHADAP POLA DISTRIBUSI LAZ - SITI MARDIYAH; MAHMUD ALFAN JAMIL (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2016)
Allocation efficiency Theory explained that if existing endowment allocation depleted, so efficiency allocation is achieved. This concept does not explain whether the existing endowment distribution have been done justice. So injustice distribution can be resolved. In Islamic Economic there is a revenue distribution system fulfillment with priority scale. The indicator of need based on Maqoshid Syariah. This research describe allocation efficiency based on Maqoshid Syariah to distribution pattern LAZ in Palembang took LAZ Dompet Duafa as a sample. This research to citation the collection and distribution fund of ZIS Dompet Duafa from 2014-2015. This research is explorative semantic analysis and domain analysis to citation work program within the framework Maqoshid Syariah. The result is distribution pattern show that Dompet Duafa still efficient and remain as institution which able to increase production possibility frontier to achieve human welfare.